2021
DOI: 10.1159/000516869
|View full text |Cite
|
Sign up to set email alerts
|

Adult Height in 299 Patients with Turner Syndrome with or without Growth Hormone Therapy: Results and Literature Review

Abstract: <b><i>Context:</i></b> Treatment with growth hormone (GH) is considered effective in improving adult height (AH) in Turner syndrome (TS). However, there are few studies comparing AH between treated patients and a concurrent untreated group. <b><i>Objective:</i></b> To assess the efficacy of GH treatment in improving AH in TS and to review previous published studies with treated and untreated groups. <b><i>Participants and Methods:</i></b> … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…In the same year, examining the prevalence estimates of specific substances, the amoxicillin/clavulanic acid combination was the most prescribed product in Group J, with values of prevalence and prescription per 1000 cases of 31.1% and 715.5, respectively, which were almost double those observed in the general population [10], but were comparable with the estimate recorded for the children 0-18 years of age residing in a city in Southern Italy [25]. Another example is provided by the consumption of somatropin (582.9 vs. 15.9 prescriptions per 1000 cases in RD patients and in the Italian general population, respectively) [10], which may be attributable to specific rare conditions such as Turner syndrome, Prader-Willi syndrome, Noonan syndrome and Russell-Silver syndrome, which together represented nearly 30% of the pediatric patients who received at least one prescription of a drug for the nervous system, and in whom long-term growthhormone treatment has been associated with significant improvements in height and body composition [26][27][28][29]. The highest value for consumption was found in Group N, probably as a consequence of the massive use of antiepileptics, particularly valproic acid, for which there were over 1000 prescriptions per 1000 cases (vs. 52.4 prescriptions per 1000 inhabitants in the national pediatric population in 2018) (Italian Medicines Agency, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the same year, examining the prevalence estimates of specific substances, the amoxicillin/clavulanic acid combination was the most prescribed product in Group J, with values of prevalence and prescription per 1000 cases of 31.1% and 715.5, respectively, which were almost double those observed in the general population [10], but were comparable with the estimate recorded for the children 0-18 years of age residing in a city in Southern Italy [25]. Another example is provided by the consumption of somatropin (582.9 vs. 15.9 prescriptions per 1000 cases in RD patients and in the Italian general population, respectively) [10], which may be attributable to specific rare conditions such as Turner syndrome, Prader-Willi syndrome, Noonan syndrome and Russell-Silver syndrome, which together represented nearly 30% of the pediatric patients who received at least one prescription of a drug for the nervous system, and in whom long-term growthhormone treatment has been associated with significant improvements in height and body composition [26][27][28][29]. The highest value for consumption was found in Group N, probably as a consequence of the massive use of antiepileptics, particularly valproic acid, for which there were over 1000 prescriptions per 1000 cases (vs. 52.4 prescriptions per 1000 inhabitants in the national pediatric population in 2018) (Italian Medicines Agency, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the growth hormone effects in our cohort were slightly lower than those in other countries. The largest recent retrospective Brazilian study reported a mean height difference of 6.2 cm between non-treated TS patients and those treated with GHT for approximately five years on a standard dose [17]. A metaanalysis of nine randomized controlled trials using recombinant GHT concluded that treated TS girls were, on average, 7.2 cm taller than non-treated patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal ascertainment has been limited primarily to those with serious structural cardiac defects and lymphedema. Women with 45,X may be diagnosed later due to phenotypic differences which are amenable to modification when identified early 35,36 , including: reduced height 37 , pubertal delay 37 , recurrent pregnancy loss and infertility 38,39 .…”
Section: Discussionmentioning
confidence: 99%